Neural mechanisms of single corrective steps evoked in the standing rabbit. (7th April 2017) - Hsu, L.-J.; Zelenin, P.V.; Lyalka, V.F.; Vemula, M.G.; Orlovsky, G.N.; Deliagina, T.G.
Highlights: Postural corrections which include single steps performed in different directions are observed in both quadrupeds and humans. We studied neural mechanisms of postural response to distortion of the body configuration caused by the limb displacement. Displacement of the limb in any direction evokes its step in opposite direction preceded by a trunk corrective movement. Corrective trunk and limb movements are generated by separate mechanisms activated by sensory signal from the displaced limb. Neuronal networks generating trunk and limb corrective movements reside in the brainstem, cerebellum, and spinal cord. Abstract: Single steps in different directions are often used for postural corrections. However, our knowledge about the neural mechanisms underlying their generation is scarce. This study was aimed to characterize the corrective steps generated in response to disturbances of the basic body configuration caused by forward, backward or outward displacement of the hindlimb, as well as to reveal location in the CNS of the corrective step generating mechanisms. Video recording of the motor response to translation of the supporting surface under the hindlimb along with contact forces and activity of back and limb muscles was performed in freely standing intact and in fixed postmammillary rabbits. In intact rabbits, displacement of the hindlimb in any direction caused a lateral trunk movement toward the contralateral hindlimb, and then a corrective step in the direction opposite to the initial displacement. The time difference between onsets of these two events varied considerably. The EMG pattern in the supporting hindlimb was similar for all directions of corrective steps. It caused the increase in the limb stiffness. EMG pattern in the stepping limb differed in steps with different directions. In postmammillary rabbits the corrective stepping movements, as well as EMG patterns in both stepping and standing hindlimbs were similar to those observed in intact rabbits. This study demonstrates that the corrective trunk and limb movements are generated by separate mechanisms activated by sensory signals from the deviated limb. The neuronal networks generating postural corrective steps reside in the brainstem, cerebellum, and spinal cord.